Thermospheric gravity waves in Fabry-Perot Interferometer measurements of the 630.0nm OI line - E. A. K. Ford; A. L. Aruliah; E. M. Griffin; I. McWhirter (Annales Geophysicae, 2006)
Gravity waves are an important feature of mesosphere - lower thermosphere (MLT) dynamics, observed using many techniques and providing an important mechanism for energy transfer between atmospheric regions. It is known that some gravity waves may propagate through the mesopause and reach greater altitudes before eventually "breaking" and depositing energy. The generation, propagation, and breaking of upper thermospheric gravity waves have not been studied directly often. However, their ionospheric counterparts, travelling ionospheric disturbances (TIDs), have been extensively studied in, for example, radar data. At high latitudes, it is believed localised auroral activity may generate gravity waves in-situ. Increases in sensor efficiency of Fabry-Perot Interferometers (FPIs) located in northern Scandinavia have provided higher time resolution measurements of the auroral oval and polar cap atomic oxygen red line emission at 630.0 nm. A Lomb-Scargle analysis of this data has shown evidence of gravity wave activity with periods ranging from a few tens of minutes to several hours. Oscillations are seen in the intensity of the line as well as the temperatures and line of sight winds. Instruments are located in Sodankylä, Finland; Kiruna, Sweden; Skibotn, Norway, and Svalbard in the Arctic Ocean. A case study is presented here, where a wave of 1.8 h period has a phase speed of 250 ms -1 with a propagation angle of 302°, and a horizontal wavelength of 1600 km. All the FPIs are co-located with EISCAT radars, as well as being supplemented by a range of other instrumentation. This allows the waves found in the FPI data to be put in context with the ionosphere and atmosphere system. Consequently, the source region of the gravity waves can be determined.